Improving Personalized Web Search using Result Diversification - Radlinski, Filip; Dumais, Susan (Proceedings of the Conference on Research and Development in Information Retrieval (SIGIR), 2006)
We present and evaluate methods for diversifying search results to improve personalized web search. A common personalization approach involves reranking the top N search results such that documents likely to be preferred by the user are presented higher. The usefulness of reranking is limited in part by the number and diversity of results considered. We propose three methods to increase the diversity of the top results and evaluate the eﬀectiveness of these methods.